The practical aspects of enteral nutrition in preterm infants - Rahmi Örs (Hygeia Press di Corridori Marinella, 2013)
Preterm infants have higher nutrient requirements than term infants. Enteral tube feeding is the preferred route to feed preterm infants because premature infants are unable to coordinate sucking, swallowing, and breathing. There are two common tube feeding methods: intermittent (bolus) or continuous infusion. Minimal enteral nutrition or trophic feeding has many advantages for preterms and should be started as soon as possible if an infant is clinically stable. Mother's own milk is the best food for preterm infants. It also has many important non-nutrient advantages for preterm infants. However, breast milk alone may not meet their special nutritional needs. For this reason, it is common clinical practice to fortify human milk. Fortified human milk is an appropriate nutritional source for preterm infants compared to preterm formula and unfortified human milk. Fortification of maternal breast milk begins when feeding volume reaches 100 ml/kg/day. In the absence of mother's own milk, donor milk and premature infant formula may be used. The aim of this brief review is to discuss the current practical concepts about enteral feeding in preterm infants.